Answer:
Step-by-step explanation:
Apply exponent rule [tex]a^{-b}=\dfrac{1}{a^b}[/tex]:
[tex]\implies \left( \dfrac{49}{16} \right) ^{-{\frac32}}=\dfrac{1}{\left( \dfrac{49}{16} \right) ^{\frac32}}[/tex]
Apply exponent rule [tex]\left( \dfrac{a}{b} \right) ^c=\dfrac{a^c}{b^c}[/tex]:
[tex]\implies \dfrac{1}{\left( \dfrac{49}{16} \right) ^{\frac32}}=\dfrac{1}{\left( \dfrac{49^{\frac32}}{16^{\frac32}} \right) }[/tex]
Factor the 49 and 16:
[tex]\implies \dfrac{1}{\left( \dfrac{49^{\frac32}}{16^{\frac32}} \right) }=\dfrac{1}{\left( \dfrac{(7^2)^{\frac32}}{(4^2)^{\frac32}} \right) }[/tex]
Apply exponent rule [tex](a^b)^c=a^{bc}[/tex]:
[tex]\implies \dfrac{1}{\left( \dfrac{(7^2)^{\frac32}}{(4^2)^{\frac32}} \right) }= \dfrac{1}{\left( \dfrac{7^3}{4^3} \right) }=\dfrac{1}{\left( \dfrac{343}{64} \right) }[/tex]
Apply fraction rule [tex]\dfrac{1}{\frac{a}{b}}=\dfrac{b}{a}[/tex]
[tex]\implies \dfrac{1}{\left( \dfrac{343}{64} \right) }=\dfrac{64}{343}[/tex]